Highly efficient electrocatalytic oxygen evolution over atomically dispersed synergistic Ni/Co dual sites - Pei, Zhihao (2022)
Single-atom catalysts (SACs) are being pursued as economical electrocatalysts. However, their low active-site loading, poor interactions, and unclear catalytic mechanism call for significant advances. Herein, atomically dispersed Ni/Co dual sites anchored on nitrogen-doped carbon (a-NiCo/NC) hollow prisms are rationally designed and synthesized. Benefiting from the atomically dispersed dual-metal sites and their synergistic interactions, the obtained a-NiCo/NC sample exhibits superior electrocatalytic activity and kinetics towards the oxygen evolution reaction. Moreover, density functional theory calculations indicate that the strong synergistic interactions from heteronuclear paired Ni/Co dual sites lead to the optimization of the electronic structure and the reduced reaction energy barrier. This work provides a promising strategy for the synthesis of high-efficiency atomically dispersed dual-site SACs in the field of electrochemical energy storage and conversion.